An audit of transfers for neonatal surgical care in England in 2007. Issue 4 (18th November 2008) - Burge, D; Youle, L; McIntosh, N
Abstract : Objective: To audit the access to specialist services for infants requiring transfer for surgical care in the neonatal networks in England in 2007. Methods: Data on neonates transferred for surgical care from January to December 2007 were obtained from the National Neonatal Audit Programme database. Information on origin and destination of transfer was used to assess what proportion of infants required transfer to another network or, in the six network centres without a surgical service, to a more distant surgical centre than appropriate. Results: Information was available from 18 of the 24 neonatal networks and identified 484 infants transferred for surgery for whom complete data were available. Ninety-one infants (18.8%) were transferred out of network or to a more distant centre than appropriate. This compares with 3.6% for all network patients and far exceeds the maximum figure of 5% recommended by the National Audit Office. Only one network was able to use a single surgical centre for transfers, and the median number of surgical units accessed in the year was 3 (range 1–8). Conclusions: Neonates requiring surgical care in England often need transfer beyond the local network. The reasons for this need further investigation by a prospective audit of access to neonatal surgical care.